Hospitalizations and deaths associated with Herpes Simplex Virus (HSV) infection in Brazil from 2012 to 2021 (Research, Society and Development, 2022)
The present study aimed to carry out an analysis of cases of hospitalizations and deaths by HSV in Brazil. For this, a descriptive, retrospective and cross-sectional study was carried out, based on the 10th revision of the International Classification of Diseases (ICD-10): B00 - Herpes virus infections (herpes simplex). The information was retrieved from Departamento de Informática do Sistema Único de Saúde (DATASUS), and “Morbidade Hospitalar do SUS (SIH/SUS)” was accessed. Between 2012 and 2021, in Brazil, 13,417 hospitalizations for herpes simplex were reported, especially in the Southeast region (n=5,077), however, the Northeast region was also highlighted with the increase in the number of hospitalizations after 2020. São Paulo was the state with the highest number of hospitalizations, with females being the most prevalent. Considering the age group, there was a prevalence in children aged 1 to 4 years, followed by the group ≥ 60 years of age. The internment regime was predominantly public and white breed. Regarding expenses, a large part was directed to the elderly, who also recorded the highest number of deaths, among females and white breed. Thus, the data presented and discussed provide important information for an assessment of the characteristics of hospitalizations and deaths from herpes simplex, providing evidence that can serve as a basis for the formulation of public policies aimed at this infection.